THE IMPACT OF DIFFERENT SOCIAL CLASSES IN LOUISA MAY ALCOTT’S NOVEL LITTLE WOMEN - Utami, Dinda Dwi; Suhendi, Andang (JOURNAL OF LANGUAGE, 2025)
This study examines how social class differences are portrayed and how they affect the protagonists in Louisa May Alcott’s Little Women. Using Marxist literary theory, the analysis focuses on class distinctions between the upper and lower classes and explores their implications for social behavior and personal identity. The qualitative descriptive method is applied to textual data gathered from close reading of the novel and relevant critical sources. The findings indicate that social class has significant impacts on the characters’ lives, manifested through experiences of bullying, jealousy, and internalized social inequality. The protagonists, particularly Meg and Amy March, face emotional conflict and social exclusion as consequences of their lower-class status. These experiences not only reveal structural injustices but also reflect broader capitalist social dynamics that define access to power, privilege, and self-worth. The study concludes that Little Women remains a valuable text for understanding how literature mirrors the enduring social hierarchies that shape human experience.